Personnel Attitude toward Power Distance in Hospitals Affiliated by Qazvin University of Medical Sciences - Sima Rafiei; Pejman Sadeghi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Human resources have a significant role in improving organizational performance specifically in healthcare institutions. This study aimed to study the hospital staff perception toward power distance in 2016. Methods: A cross sectional, descriptive study was conducted among 668 hospital staff affiliated by Qazvin University of Medical Sciences. A standard questionnaire developed by Hofstede consisted of 31 questions in seven domains including hierarchy, reward, climate, communication, decision making, learning and management was applied to gather data. SPSS Software package version 20 was used to analyze data using descriptive statistics (mean, standard deviation), t-test and ANOVA analysis. Results: Study findings showed a low level of power distance perceived by employees (mean score = 67.6 ± 2.3). The most inequality perceived by study staff belonged to decision making aspect and the method of applying managerial authority in the organization.  Conclusion: Applying strategies to improve staff participation in work decisions and job responsibilities would help organizations maintain and develop employees with positive perception toward justice.